2003
DOI: 10.4269/ajtmh.2003.69.565
|View full text |Cite
|
Sign up to set email alerts
|

ASSOCIATION OF Fcγ RECEPTOR IIa (CD32) POLYMORPHISM WITH SEVERE MALARIA IN WEST AFRICA

Abstract: Malaria continues to claim the lives of more children worldwide than any other infectious disease, and improved understanding of disease immunology is a priority for the development of new therapeutic and vaccination strategies. Fc␥RIIa (CD32) contains a polymorphic variant (H/R131) that has been associated with variability in susceptibility to both bacterial diseases and Plasmodium falciparum parasitemia. We investigated the role of this polymorphism in West Africans with mild and severe malarial disease. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
63
2
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(73 citation statements)
references
References 21 publications
6
63
2
2
Order By: Relevance
“…Some studies, but not others, have found an increased risk of invasive pneumococcal or meningococcal disease with the RR genotype (31,32,41,42). In contrast, RR patients may be protected from severe malaria (33). Thus, in diseases associated with pathogenic or infectious immune complexes, the less efficiently phagocytic RR genotype is disadvantageous.…”
Section: Discussionmentioning
confidence: 98%
“…Some studies, but not others, have found an increased risk of invasive pneumococcal or meningococcal disease with the RR genotype (31,32,41,42). In contrast, RR patients may be protected from severe malaria (33). Thus, in diseases associated with pathogenic or infectious immune complexes, the less efficiently phagocytic RR genotype is disadvantageous.…”
Section: Discussionmentioning
confidence: 98%
“…Like opsonic phagocytosis, monocyte-mediated antibody-dependent inhibition of the in vitro growth of parasites (3,24,32,36,48,56) positively correlates with in vivo protection (3). The central importance of Fc receptor biology in malaria is indicated by the observation that polymorphisms in Fc receptors modify the outcome of infection (8,10,40,47,65).We tested the hypothesis that sequence diversity in MSP2 renders parasites bearing heterologous MSP2 alleles differentially susceptible to Fc-dependent functions of allele-specific MSP2 antibodies. Antibodies from clinically immune adults living in regions where malaria is endemic were isolated using long synthetic peptides of the family-specific MSP2 sequences devoid of the adjoining conserved domain.…”
mentioning
confidence: 99%
“…The gene that encodes FcgRIIa, FCGR2A (1q23), is predominantly expressed on neutrophils and carries a functional SNP that substitutes an arginine (R) to histidine (H) at position 131. Compared with wildtype 131R homozygotes, 131 homozygotes have high binding affinity for IgG2 and have been associated with a number of infectious [46][47][48] and autoimmune diseases. 49,50 Given that MM is characterized, in part, by an accumulation of IgG-producing monoclonal plasma cells, it is possible that variants in FCGR2A may contribute either directly or indirectly to the genetic susceptibility profile associated with the etiology of this B-cell malignancy.…”
Section: Discussionmentioning
confidence: 99%